Defining "Information Resources" and Their Interpretation in the Domain of Ukrainian National Police - Mykievych, Mykhailo; Senyk, Sviatoslav; Krayevska, Oksana (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2021)
The article focuses on studying the definitions of “information technologies” and aims to elaborate on the proposal concerning its legislative consolidation. The analysis of actual regulations in Ukraine, which determine the public relations in the sphere of information, as well as the state of research on this problem by other scholars, have shown the following: (1) currently, there is no unambiguous interpretation of this definition at the legislative level, which creates the preconditions for ambiguous interpretation and practical application of this concept in the legal field; (2) for several reasons, there exists a noticeable lack of a unanimous approach to unifying the definitions of “information resources.” This study offers to rely on an approach according to which the definition of “information resources” is considered in the context of a particular area of social activities. Based on this approach, it is offered to amend the basic normative legal document that defines public relations in the information sphere in Ukraine, i.e., the Law of Ukraine “On Information,” as well as the main legal instrument that regulates information activities in the National Police of Ukraine, that is the Law of Ukraine “On the National Police.”

Artykuł poświęcony jest badaniu definicji „zasobów informacyjnych” oraz opracowywaniu propozycji ich konsolidacji legislacyjnej. Analiza aktualnych przepisów Ukrainy regulujących public relations w sferze informacyjnej oraz wyniki badań na ten temat naukowców z różnych dziedzin wiedzy wykazały, że obecnie na poziomie legislacyjnym brak jest jednoznacznej interpretacji tej definicji, co stwarza przesłanki do niejasności interpretacyjnych i praktycznego zastosowania. Z wielu powodów brakuje jednomyślności w podejściu do sformułowania ujednoliconej definicji „zasobów informacyjnych” należy rozpatrywać w kontekście określonego obszaru działalności publicznej. W oparciu o to podejście proponuje się nowelizację podstawowego dokumentu normatywnego określającego public relations w sferze informacyjnej na Ukrainie – ustawy ukraińskiej „O informacji”, a także głównego dokumentu normatywnego regulującego działalność informacyjną w Policji Państwowej – ustawy Ukrainy „O policji narodowej”.
Definicja "zasobów informacji" i jej interpretacja w zakresie działania policji narodowej Ukrainy
Keywords: information; information resources; information services; normative-legal regulation; National Police of Ukraine; public relations; informacja; zasoby informacyjne; działalność informacyjna; regulacja prawna; Ukraińska Policja Państwowa; public relations